2019
DOI: 10.1111/ijlh.13102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different preanalytical conditions on results of lupus anticoagulant tests

Abstract: Introduction:The currently recommended preanalytical conditions for lupus anticoagulant (LA) analysis require analyzing samples in fresh or freshly frozen platelet-poor plasma. The aim of this study was to evaluate whether alternative and less cumbersome preanalytical procedures for LA testing give significantly different results compared to recommended conditions. Materials and Methods: Citrated blood samples were drawn from 29 study participants, 15 with negative and 14 with positive LA results. The samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The lowest platelet count (<3×10 3 /µL) was obtained from the 1,500 g centrifugation technique for 15 minutes twice. This result was similar to a previous study conducted by Kristoffersen and Sicard which showed that the number of platelets of PPP produced by doing 1,500 g of centrifugation for 15 minutes twice and 3,260 g of centrifugation in 10 minutes was <10,000/ µL [6,11] . This study was the first study to examine the centrifugation of 3,000 g for 15 minutes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The lowest platelet count (<3×10 3 /µL) was obtained from the 1,500 g centrifugation technique for 15 minutes twice. This result was similar to a previous study conducted by Kristoffersen and Sicard which showed that the number of platelets of PPP produced by doing 1,500 g of centrifugation for 15 minutes twice and 3,260 g of centrifugation in 10 minutes was <10,000/ µL [6,11] . This study was the first study to examine the centrifugation of 3,000 g for 15 minutes.…”
Section: Discussionsupporting
confidence: 91%
“…The preparation of PPP recommended by the Clinical and Laboratory Standart Institute (CLSI) is to use a tube with sodium citrate anticoagulant and centrifugation processes at a speed of 1,500 g for at least 15 minutes [5] . Different results were obtained in a study conducted by Kristoffersen which stated that the number of platelets after a single 1,500 g centrifugation results in a platelet count <22,000/µL [6] . Magnette et al recommend a repeat of centrifugation to ensure platelet residue is less than 10,000/µL.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…21 It is common to freeze plasmas for batched analysis at a later date which exacerbates this problem because the freeze/thaw process ruptures platelet membranes, resulting in excess PL in the plasma samples and risking further LA quenching. 22 Ultracentrifugation might seem a straightforward alternative but is discouraged as it can generate platelet microparticles capable of quenching LA. 6,7,23 Filtering plasma through 0.22-µm cellulose acetate filters will remove all platelets but is also discouraged because of microparticle generation, and additionally, it can induce loss of von Willebrand factor (VWF) and some coagulation factors.…”
Section: Pre-examination Considerationsmentioning
confidence: 99%
“…In most cases, laboratories can safely use manufacturer's or published study information to determine the stability of the specimen, but in some conditions the stability of the specimen is not available yet [3,4,5,6] . Because of this reason, research related to recommendations of storage and examination time on the stability of PPT and aPTT blood specimens in the testing of coagulation physiology in Dr. Soetomo Hospital laboratory is very important, considering that the results of an accurate, fast, and precise testing is closely related to the financing and quality of blood testing services at Dr. Soetomo Hospital, Surabaya, Indonesia.…”
Section: Introductionmentioning
confidence: 99%